Evaluation of Chocolate Drink Processing Process Related to Guarantee of Halal Products (Case Study on CV. Sultan Agro Maritim Industri in Kendari City) - Susanto, Riki; Rianda, La; Thamrin, Thamrin (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
This research aims to evaluate the Chocolate Drink Processing Process of Halal Product Guarantees (Case Study: CV. Sultan Agro Maritim Industri in Kendari City). The research was designed using a case study method with a qualitative approach. Data collection was carried out using interviews, observation, and recording tape studies. The research results show that there are 3 research focus points, including (a) halal ingredients, (b) production facilities, and (c) products found in the chocolate drink processing process. Types of raw materials used (cocoa powder), cocoa beans, production facilities (supply of ingredients, processing, storage, packaging, sales), and products (chocolate drinks). Several factors influence the guarantee of halal products in the process of making chocolate drinks, including ingredients, products, and production facilities. The materials used are halal in terms of their substances, how to obtain the materials, and how they are processed. There are no products produced with brands or names that lead to haram, and sensory characteristics such as smell and taste are avoided in haram products. The same thing also applies to the production facilities used in making chocolate drinks, which are protected from haram ingredients, maintain cleanliness and purity, and ensure that there is no contamination from haram materials or products.